Congenital erythropoietic porphyria: Two case reports - Sankha Koley; Vikrant Saoji (Wolters Kluwer Medknow Publications, 2011)
Porphyrias form a group of disorders caused due to defects in the haem synthetic pathway. Congenital erythropoietic porphyia (CEP) is the rarest of the bullous porphyrias (less than 200 cases have been reported till recent times) and a clinician may not see a case during his professional life. We present two cases of CEP. One child with CEP presented with typical infancy-onset blistering, photosensitivity, red urine, and erythrodontia, with hypertrichosis of the upper arms and back. The other child of CEP presented with childhood-onset blistering, mutilation, and hypertrichosis on the face.